Blog Popularity and Activity on Social Media: An Exploratory Research - Bhat, Anil (Indian Journal of Marketing, 2012)
Web 2.0 is a new revolution and at its core lies social media, which is certainly the new medium that the researchers are trying to understand and marketers are planning to use much more effectively. This paper explores various social media marketing techniques that are responsible for bringing about this revolution. This paper tries to relate one of the most popular web 2.0 phenomenon of that of blogging with other equally growing social-networking sites Facebook® and Twitter® usage. A study is conducted across four blog categories to determine the correlations between blog popularity (using a measure of page views), and their activity on social-networking sites viz Facebook® and Twitter®. As it is true with the growing influence of social media as a marketing medium, we find a positive correlation between blog popularity and activity on social media.